2022
DOI: 10.1002/jpen.2411
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a best‐practice guideline: Early enteral nutrition in a neuroscience intensive care unit

Abstract: Current evidence suggests that early enteral nutrition is a best practice and leads to improved clinical outcomes. An evidence‐based practice project was implemented in a busy neurointensive care unit in a midwestern tertiary care facility that was designed to improve care by implementing the early nutrition portion of Guidelines for the Provision and Assessment of Nutrition Support Therapy in the Adult Critically Ill Patient: Society of Critical Care Medicine and the American Society for Enteral and Parentera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…The quasi-experimental studies [ 53 , 54 ] and the retrospective study [ 45 ] have been classified as having a low risk of bias because they had a more robust design with a greater capacity to control errors [ 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The quasi-experimental studies [ 53 , 54 ] and the retrospective study [ 45 ] have been classified as having a low risk of bias because they had a more robust design with a greater capacity to control errors [ 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was noted that EN-related nursing care was consistently documented when associated with other patient priorities, with EN being given higher priority in more stable patients [ 56 ]. Surveys conducted by several authors [ 46 , 48 , 54 ] (prior to the implementation of the contemplated nutrition education program) found that the main individual and team barriers to initiating optimal EN were feeding intolerance, standard nursing practices, severity of illness, lack of knowledge and beliefs that new guidelines would not change current practices. After the educational interventions were implemented [ 54 ], the level of knowledge of professionals regarding EN improved by up to 81%, interdisciplinary communication increased and feeding initiation times and complications were reduced [ 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations